1997
DOI: 10.1002/(sici)1096-8628(19971219)73:3<267::aid-ajmg7>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Tandem duplication of 11p12-p13 in a child with borderline development delay and eye abnormalities: Dose effect of the PAX6 gene product?

Abstract: We report on a girl with a duplication of chromosome band 11p12-->13, which includes the Wilms tumor gene (WT1) and the aniridia gene (PAX6). The girl had borderline developmental delay, mild facial anomalies, and eye abnormalities. Eye findings were also present in most of the 11 other published cases with partial trisomy 11p, including 11p12-->13. Recently, it was shown that introduction of additional copies of the PAX6 gene into mice caused very variable eye abnormalities. Therefore, a PAX6 gene dosage effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 15 publications
0
20
0
1
Order By: Relevance
“…This is not an eVect commonly mimicked by intragenic mutation and it is thus more diYcult to assign pathogenesis to individual genes without animal model clues. Overexpression of PAX6 causes eye malformations in transgenic mice (Schedl et al 1996), and eye abnormalities were also reported in patients carrying a duplication including the PAX6 locus on 11p13 (Aalfs et al 1997) Several HPE duplication MABs were found (Table 3). Six patients from HCD were reported to have dup(3p) including MABs 3p25-p26 (P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…This is not an eVect commonly mimicked by intragenic mutation and it is thus more diYcult to assign pathogenesis to individual genes without animal model clues. Overexpression of PAX6 causes eye malformations in transgenic mice (Schedl et al 1996), and eye abnormalities were also reported in patients carrying a duplication including the PAX6 locus on 11p13 (Aalfs et al 1997) Several HPE duplication MABs were found (Table 3). Six patients from HCD were reported to have dup(3p) including MABs 3p25-p26 (P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Over-expression of Pax6 in hemizygous PAX77 Tg/− mice with 5–7 copies of human PAX6 [8] also causes eye abnormalities on a wild-type (WT) background and provides a model for human PAX6 gene duplication [7]. The abnormalities overlap with those produced by heterozygous Pax6 +/− mice (low Pax6 levels) but there are significant differences and genetic background modulates the phenotype [8], [52]–[55].…”
Section: Introductionmentioning
confidence: 99%
“…The genetic defect underlying aniridia is haploinsufficiency of PAX6, caused by mutations in the PAX6 gene [45] or by either deletions/duplications affecting the PAX6 gene directly [46] or in downstream enhancer regions [47]. Although developing into a panocular condition, aniridia is initially characterized by partial or complete iris hypoplasia commonly associated with varying degrees of foveal hypoplasia and poor visual acuity in early infancy [48].…”
Section: Aniridiamentioning
confidence: 99%